Cognitive function and adherence of older adults undergoing hemodialysis. (Nephrology Nursing Journal)
As the number of older adults undergoing hemodialysis increases, it is important for nurses to consider cognitive impairment as a contributing factor to non-adherence. The purpose of this exploratory study was to identify cognitive markers that nurses can use to alert them to potential problems with adherence among older adults undergoing hemodialysis. Stories of the health challenge of making lifestyle change were analyzed with a linguistic analysis software program. A standardized instrument (3MS) that measures global cognitive function was administered. Determination of adherence level was the last activity of data collection. In this sample (n=63), 39.7% of the participants had evidence of cognitive impairment (3MS score less than 80); 58.2% of the 39.7% had evidence of non-adherence. There was a significant relationship between word use and cognitive function (p < .01). Cognitive impairment is prevalent among older adults undergoing hemodialysis and words might be a proxy for recognizing this.